2017
DOI: 10.1016/j.alcohol.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol intake in two different mouse drinking models after recovery from the lipopolysaccharide-induced sickness reaction

Abstract: Neuroinflammation may play an important role in the development of alcohol addiction. Recent preclinical reports suggest that enhanced innate immune system signaling increases consumption of alcohol. Our aim was to study whether consequences of lipopolysaccharide (LPS)-induced sickness reaction increase long-term alcohol intake. Adult male C57BL/6J mice, housed in individually ventilated cages, were injected with LPS intraperitoneally (i.p.) and allowed to recover from an acute sickness reaction for 1 week bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Pharmacological and genetic manipulations of neuroinflammatory targets have yielded promising results in reducing alcohol consumption across these different paradigms. For example, inhibition of microglia activation reduces alcohol consumption during the DID task in C57/BL6 male mice (Lainiola and Linden, 2017) and prevents relapse-like drinking in the 2BC task in male rats (Gajbhiye et al, 2018). Further, inhibition of microglial P2X7 receptor signaling also reduces alcohol consumption in C57/BL6 male mice during the DID paradigm (Lainiola and Linden, 2017).…”
Section: Alcoholmentioning
confidence: 99%
“…Pharmacological and genetic manipulations of neuroinflammatory targets have yielded promising results in reducing alcohol consumption across these different paradigms. For example, inhibition of microglia activation reduces alcohol consumption during the DID task in C57/BL6 male mice (Lainiola and Linden, 2017) and prevents relapse-like drinking in the 2BC task in male rats (Gajbhiye et al, 2018). Further, inhibition of microglial P2X7 receptor signaling also reduces alcohol consumption in C57/BL6 male mice during the DID paradigm (Lainiola and Linden, 2017).…”
Section: Alcoholmentioning
confidence: 99%
“…It is not clear enough and a focus of debate whether the alcohol-induced neuroinflammation would play a role in alcohol consumption. Some studies fail to detect a link between alcohol-induced neuroinflammation and drug consumption (Lainiola and Linden, 2017), and genetic and pharmacologic manipulation of TLR4 has been shown to have a minimal impact on rodent ethanol consumption (Harris et al, 2017). On the contrary, recent studies using anti-inflammatory mesenchymal stem cells suggest that targeting neuroinflammation could be an effective therapeutic approach to reduce alcohol consumption and relapse (Ezquer et al, 2018, 2017).…”
Section: Effects Of Oea In Alcohol Consumption and Negative Behaviorsmentioning
confidence: 99%
“…However, despite evidence that TLR4/MyD88-dependent signaling is important for alcohol responses, it was recently found that TLR4 is not a critical determinant of excessive drinking in animal models (20,21). Moreover, a recent study could not replicate that LPS pretreatment increases alcohol consumption in continuous two-bottle-choice or drinking-in-the-dark (22). This suggests that other innate immune pathways may be important in the regulation of excessive alcohol consumption.…”
Section: Introductionmentioning
confidence: 98%